Disciple - Stephen Coonts (Britain Quercus, 2010)
Tommy Carmellini and Jake Grafton have information that Iran's covert nuclear programme is nearing completion. The Iranian president is planning to hit US and Israeli targets within days and turn Iran into a nation of martyrs, leading the world's Moslems in a holy war against the unbelievers. Carmellini has a secret weapon, a group of Iranian dissidents who will do anything to stop the attack. But will the US government believe him in time to act?
Keywords: American fiction